Analisis Sentimen dalam Opini Publik di Chanel Youtube Indonesia Lawyers Club Tentang Isu Populer dengan Menggunakan Metode LSTM dan Bi-LSTM - Wicaksono, Bagus; Nastiti, Vinna Rahmayanti Setyaning (Jurnal Algoritma, 2024)
One of the social media that often shares news and is popularly used in Indonesia is YouTube. Through the YouTube platform readers can leave comments to share their opinions under related news. This news and commentary has been a great source of information and research. This article presents a data set containing 368,299 public comments and replies from 73 video news published from 01 January 2024 to 18 May 2024 from the famous “YouTube Indonesia Lawyers Club” channel. To ensure commenter privacy, commenter names are coded in the dataset. This dataset is open for use by researchers with the access link https://data.mendeley.com/datasets/h9335fgsgr/1. This data can help researchers identify patterns in public opinion and analyze how public opinion changes over time. The news topic most liked by the public is related to the Jokowi government, resulting in an accuracy value for the LSTM method of 99.61% while with the LSTM method the accuracy is 98.11%.